Exploring the Dynamics of Digitalization in Zakat and Waqf Management: A Case Study of UPZ Baznas YAKIN - Arifin, Moh; Majid Toyyibi, Abdul; Oktavia, Rima (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study aims to describe the opportunities and challenges of digitalization in the management of zakat and waqf at the Zakat Collection Unit (UPZ) of BAZNAS Yayasan Al Khidmah Indonesia (YAKIN). Using a descriptive qualitative approach, data were collected through in-depth interviews with UPZ administrators and analyzed narratively. The results of the study indicate that digitalization has had a positive impact on the efficiency of collecting and distributing religious social funds, as well as enhancing institutional transparency and legitimacy. UPZ BAZNAS YAKIN has utilized various digital platforms such as websites, social media, QRIS, and bank accounts, although it still faces obstacles such as limited funding and a lack of digital training. This research shows that digitalization plays a strategic role in building public trust and expanding community participation, and serves as an adaptive step in response to the dynamics of modern Islamic social finance. The study emphasizes the importance of technological innovation in strengthening institutional capacity and optimizing the potential of zakat and waqf in the era of digital transformation.